2008
DOI: 10.1094/phyto-98-4-0443
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Fitness of Anilinopyrimidine-Resistant Strains of Botrytis cinerea

Abstract: The fitness of anilinopyrimidine-resistant isolates of Botrytis cinerea compared with that of sensitive isolates, collected from vegetable crops in Greece during 2005, was investigated. Stability of resistance to anilinopyrimidine fungicides was determined after consecutive transfers of the fungal isolates on fungicide-free potato dextrose agar for 16 culture cycles or on fungicide-untreated cucumber seedlings for eight disease cycles. Results showed that after the consecutive transfers of the isolates either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
9

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 36 publications
2
33
0
9
Order By: Relevance
“…High variability in fitness parameters among both AP-resistant and AP-sensitive isolates was observed in a previous study, and, as a group, resistant isolates showed reduced mycelial growth and virulence (Bardas et al 2008). In the present work, APresistant isolates that were also resistant to other fungicides grew significantly more slowly than the WT isolates and formed smaller lesions on bean leaves.…”
Section: Discussionmentioning
confidence: 66%
“…High variability in fitness parameters among both AP-resistant and AP-sensitive isolates was observed in a previous study, and, as a group, resistant isolates showed reduced mycelial growth and virulence (Bardas et al 2008). In the present work, APresistant isolates that were also resistant to other fungicides grew significantly more slowly than the WT isolates and formed smaller lesions on bean leaves.…”
Section: Discussionmentioning
confidence: 66%
“…There was a high diversity of combinations of resistance mutations in German MR isolates, akin to the situation in the United States (Fernández-Ortuño et al, 2015). These and similar fungicide resistance mutations have sometimes been reported to impair the fitness of Botrytis isolates in the case of fenhexamid (Billard et al, 2012), boscalid (Lalève et al, 2013; Veloukas et al, 2014) and iprodione (Leroux et al, 2002) whereas in other studies no fitness reductions were found (Bardas et al, 2008; Fernández-Ortuño et al, 2013; Amiri et al, 2014; Veloukas et al, 2014). The availability of strains with simultaneous resistance to most or all of these fungicides provided the opportunity to analyse their combined effects on fitness by performing phenotypic comparisons of MR and sensitive field strains.…”
Section: Discussionmentioning
confidence: 84%
“…An approach to estimating the stability of resistance and fitness is the comparison of two data points: the current situation (we call here "the initial culture") with the last transfer (Bardas et al, 2008; 2014; Karaoglanidis and Thanassoulopoulos, 2002;Kim and Xiao, 2011;Vega and Dewdney, 2014), but additional data in different time point of transfers will provide a better understanding of the process (Zhan and McDonald, 2013). There is a high degree of variability in conidia production and usually the number of conidia shows linear and gradual changes between transfers (Cox et al, 2007;Fan et al, 2015;Laleve et al, 2014;Vega and Dewdney, 2014).…”
Section: Resultsmentioning
confidence: 99%